Determination of Probiotic Properties of L. fermentum MT308789 and L.oris MT308790 Isolated from Mother Breast Milk: Life Sciences-Microbiology for Health Care - Shradhdha M Gondaliya; Vimal M Ramani (International Journal of Life Science and Pharma Research, 2022)
Mother milk is a complete food for the child. It contains vital nutrients and biomolecules required for the growth and development of a child. It mainly contains carbohydrates, proteins, fats and minerals. Recently, it was also found that it contains certain different microorganisms which play a vital role in the body. Most of the microorganism of milk belongs to the Lactobacilli family. Knowing the importance of Lactobacilli in health, certain food industries have focused on these microorganisms to be used as a health supplement nowadays called probiotics. Here in this study, Lactobacilli were isolated from mother breast milk and their probiotic characteristics were studied to determine their potential for probiotic. Strains were isolated using MRS medium and analyzed for their biochemical properties, pH resistance, bile salt tolerance, NaCl concentration and antimicrobial activity. Results of the study have shown that out of two strains, one strain was L. fermentum MT308789 and other was L oris MT308790. Both the species have shown good resistance to acidic pH and bile salt. They were also having good antimicrobial activity. Based on the study it was found that both strains have potential to be used as probiotic.